Uptake of Provider Initiated HIV Testing and Counseling among women attending an urban Sexually Transmitted Disease Clinic in South Africa- missed opportunities for early diagnosis of HIV infection - Kharsany, Ayesha BM (2010)
This study assessed the uptake of Provider Initiated HIV Testing and Counseling (PITC) amongst women attending an urban sexually transmitted diseases (STD) clinic in South Africa. From July 2005 to June 2006, women were offered HIV testing following group information and education on HIV and STDs in the clinic waiting area. Of those who were provided with education, information and offered HIV testing, uptake was 43.5% (2439/5612). The overall HIV prevalence among those tested was 56.5% and the prevalence of acute HIV infection was 1.2%. Of the 56.5% (3173/5612) refusing to test, the reasons for not testing were having already been tested for HIV (61.8%), being afraid to test or felt unready to test (32.5%), the need to consult with partner (0.9%) and refusing with no explanation (4.2%). In settings where high risk patients await health care services, such as an STD clinic, failure to implement PITC is a missed opportunity for patients to benefit from counseling, prevention, early diagnosis and referral into care and treatment for HIV infection.